ANALYSIS OF PUBLIC PERCEPTIONS OF ACCOUNTABILITY AND THE NEED FOR IT-BASED FLOOD MITIGATION SYSTEMS AND URBAN INFRASTRUCTURE IN BANDUNG CITY, INDONESIA (Proceeding of SINERGY, 2026)
Climate change and rapid urbanization have greatly contributed to the increase in the frequency of flooding, including in the city of Bandung, Indonesia. To date, flooding remains a major challenge for the local government. Therefore, this study aims to examine the integration between public governance and technological innovation. Specifically, this study focuses on the community's perception of the accountability of current flood management and their views on the need to integrate information technology (IT) into urban infrastructure to improve mitigation efforts.This study uses a quantitative method with a descriptive survey method. Data were collected through a structured questionnaire distributed to residents in flood-prone areas in the city of Bandung, focusing on key variables such as perceived transparency, government responsiveness, and the urgency of digital transformation in disaster mitigation.The results show a significant difference between public expectations regarding flood management accountability and the government's current performance. The majority of respondents feel that accountability is still low due to the lack of real-time information. In addition, the data shows a high level of public urgency for the development of IT-based mitigation systems, particularly the need for predictive analytics and real-time early warning dashboards. The public views these technological tools as essential elements for building public trust and ensuring sustainable urban development. This study concludes that the Bandung City government must prioritize digital integration in its infrastructure planning. By responding to public demand for IT-based transparency, the relevant authorities can improve flood mitigation outcomes while strengthening public trust in urban governance.